Deciphering the Genomic Complexity of Acromesomelic Dysplasia Type Maroteaux: Insights from a Consanguineous Pakistani Family - Khalid, Maryam; Khalid, Mehak; Zaidi, Dua Zhaira; Zhaira, Ismat; Hashmi, Mahe- Kamil Qureshi; Begum, Shahzeera; Chaudary, Shamshad Kausar; Ahmed, Waseem (International Journal of Health Sciences, 2024)
Purpose: This study delves into the genetic basis of Acromesomelic Dysplasia (AMD), a rare skeletal disorder, particularly focusing on the Maroteaux type within a consanguineous Pakistani family. The purpose is to explore the genetic landscape beyond known mutations and understand the underlying causes of AMD. Methodology: A comprehensive approach was adopted, combining detailed clinical examinations with advanced genomic methodologies. Ethical clearance was obtained, and pedigree design facilitated the identification of affected individuals. Molecular techniques including DNA extraction and linkage analysis were conducted to investigate known AMD-related genes such as NPR2, BMPR1B, GDF5, GALNS, GLB1, and GHR. Whole-genome sequencing was emphasized despite financial constraints to uncover potential novel genetic loci associated with AMD. Findings: Despite exhaustive analysis, no mutations in known AMD-related genes were identified within the studied family. Linkage analysis did not correlate with any known genetic loci, suggesting the presence of unidentified genetic elements contributing to AMD. Autosomal recessive inheritance was confirmed through pedigree and molecular scrutiny, highlighting the complexity of AMD genetics. Unique Contribution to Theory, Policy and Practice: This research underscores the importance of employing advanced genomic strategies, such as whole-genome sequencing, in decoding rare genetic disorders like AMD. By revealing the limitations of current diagnostic approaches and advocating for collaborative efforts and resource pooling, this study contributes to the advancement of genetic counseling, therapeutic interventions, and precision medicine in rare genetic disorders.